Clinical attitude regarding denosumab drug-holiday for dental extraction in oncologic patients: a national survey - Lainé Claire; Desoutter Aline; Chaux Anne-Gaëlle (Journal of Oral Medicine and Oral Surgery, 2021)
Introduction: Denosumab is indicated in oncology to reduce tumoral development. However, this medication may cause osteonecrosis of the jaw, especially after dental extractions. Drug holiday has been proposed to decrease the risk of osteonecrosis of the jaw. This survey aimed to assess the management of drug holidays for patients who needed both dental extraction and denosumab. Methods: A questionnaire was sent to a panel of healthcare professionals. Results: Of the 33 practitioners interviewed, 28 undertook or “were used to” dental extractions in patients on denosumab. 25% (7/28) of the practitioners questioned did not stop patients from taking denosumab before dental extraction and 75% (21/28) used a drug holiday. For those who stopped the treatment, 33% (7/21) waited 2 months before performing dental extraction and 38% (8/21) waited 2 months after the dental extraction before reintroducing the molecule; 2 months being the median duration in both cases. In addition, 89% (25/28) of practitioners, modified their surgical procedure for these patients. Conclusion: Despite a small number of responders, it seemed that a drug holiday of at least 2 months is mandatory before performing tooth extraction. The issue of the drug holiday should always be raised with the patient's oncologist.